Surgical methods of treatment of extrasphincter and transsphincteric fistulas of the rectum (literature review) - I. S. Bogormistrov; S. A. Frolov; A. M. Kuzminov; A. S. Borodkin; V. Yu. Korolik; Sh. T. Minbayev (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2015)
The aim of review. To present literature data on surgical treatment of extrasphincteric and transsphincteric fistulas of rectum.Key points. Treatment of fistulas of rectum remains a challenge because of risk of frequent relapses varying from 4,7 to 60%. Radical treatment methods are overly traumatic and result in severe fibrotic changes in the anal canal structures that are accompanied by high risk of anal sphincter incompetence - up to 83%. Now highly effective methods with application of various implants to eliminate tissue defect and improve regeneration are presented in the literature more and more commonly. Application of collagenic implants allows to decrease traumatization of sphincter fibres and thus to reduce to minimum risk of anal sphincter incompetence.Conclusion. Elimination of postoperative anal incontinence is a priority task in treatment of extrasphincter fistulas of rectum.